Gambaran Pengetahuan Orang Tua tentang Diare di Rawat Jalan dan Ruang Flamboyan RSI PKU Muhammadiyah Pekajangan Pekalongan - S Suparjo; Wiwiek Natalya (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Description of Parents' Knowledge About Diarrhea in Outpatient and Flamboyant Room RSI PKU Muhammadiyah Pekajangan Pekalongan. Background: Diarrhea is an endemic disease that has the potential to become an extraordinary event (KLB) and is accompanied by death (Kemenkes RI, 2020, p164). The age group with the highest prevalence of diarrhea is in the age group of 1-4 years. Parents' knowledge about diarrhea is important to prevent diarrheal disease or death from diarrhea. Objective: This study aims to describe the knowledge of parents about diarrhea in the Outpatient and Flamboyant Room of RSI PKU Muhammadiyah Pekajangan Pekalongan. Sample: This study involved 42 parents whose children were diagnosed with diarrhea in the Outpatient and Flamboyant Room of RSI PKU Muhammadiyah Pekajangan Pekalongan. Methods: This research is descriptive, using accidental sampling technique. The research instrument used a questionnaire. Data analysis used univariate analysis with frequency distribution. Results: The results showed that 81% of respondents were in early adulthood, 54.8% had secondary education (SMA) and 73.8% worked. There are 19% of respondents have good knowledge, 62% of respondents have sufficient knowledge and 19% of respondents have less knowledge about diarrhea in children.